Screening of sugarcane genotypes against Top Borer (Scirpophaga exerptalis Walker) infestation - Paudel, Kapil; Dangi, Naresh; Ansari, Anisur Rahman; Regmi, Rashmi (Journal of Agriculture and Natural Resources, 2021)
Fourty sugarcane genotypes with different period of maturity were evaluated against top borer (Scirpophaga excerptalis Walker) infestation under natural field condition during 2018 and 2019 at National Sugarcane Research Program, Jeetpur, Nepal. The experiment was conducted in alpha-lattice design under natural condition of infestation using Co 0238 as susceptible check. Based on the incidence, 26 genotypes were categorized as less susceptible, eleven genotypes were found moderately susceptible to S. excerptalis. However, among less susceptible genotypes lowest incidence of 3.11 percent was recorded in genotype CoS 8432. Whereas, highest incidence of 25.24 percent was recorded in highly susceptible genotype, CoSe 98255BD 24. Most of the cane genotypes were found low to moderately susceptible, having 5 to 20% incidence of the pest. Whereas, some of the varieties, namely CoH 160 (21.22%), CoSe 95255 BD 24 (25.24%) and BO 150 (22.02%) were found highly susceptible. The mechanism responsible for host plant resistance against top borer is not studied in this experimentation. The study in these aspects is to be conducted to explore the mechanisms of host plant resistance for using these resistant genotypes for breeding purpose.